Porous COS@SiO2 Nanocomposites Ameliorate Severe Acute Pancreatitis and Associated Lung Injury by Regulating the Nrf2 Signaling Pathway in Mice - Mei, Qixiang; Deng, Guoying; Huang, Zehua; Yin, Yue; Li, Chunlin; Hu, Junhui; Fu, Yang; Wang, Xingpeng; Zeng, Yue (Frontiers in Chemistry, 2020)
Severe acute pancreatitis (SAP) is associated with high rates of mortality and morbidity. Chitosan oligosaccharides (COSs) are agents with antioxidant properties. We developed porous COS@SiO2 nanocomposites to study the protective effects and mechanisms of COS nanomedicine for the treatment of acute pancreatitis. Porous COS@SiO2 nanocomposites released COSs slowly under pH control, enabling sustained release and maintaining the drug at a higher concentration. This study aimed to determine whether porous COS@SiO2 nanocomposites ameliorate SAP and associated lung injury. The SAP model was established in male C57BL/6 mice by intraperitoneal injection of caerulein. The expression levels of myeloperoxidase, malondialdehyde, superoxide dismutase, nuclear factor-kappa B (NF-κB), the NOD-like receptor protein 3 (NLRP3) inflammasome, nuclear factor E2-related factor 2 (Nrf2), and inflammatory cytokines were detected, and a histological analysis of mouse pancreatic and lung tissues was performed. In the SAP groups, systemic inflammation and oxidative stress occurred, and pathological damage to the pancreas and lung was obvious. Combined with porous COS@SiO2 nanocomposites before treatment, the systemic inflammatory response was obviously reduced, as were oxidative stress indicators in targeted tissues. It was found that Nrf2 was significantly activated in the COS@SiO2 treatment group, and the expressions of NF-κB and the NLRP3 inflammasome were notably decreased. In addition, this protective effect was significantly weakened when Nrf2 signaling was inhibited by ML385. This demonstrated that porous COS@SiO2 nanocomposites activate the Nrf2 signaling pathway to inhibit oxidative stress and reduce the expression of NF-κB and the NLRP3 inflammasome and the release of inflammatory factors, thus blocking the systemic inflammatory response and ultimately ameliorating SAP and associated lung injury.